PERAN PEMBERDAYAAN KARYAWAN PADA INTENTION TO QUIT: KINERJA SEBAGAI VARIABEL MEDIASI - Danang Wahyudi,; Danang Sunyoto,; Dewanti Monica Amanda,; Fikri Budi Aulia, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
Objectives–This study aims to examine and analyze the role of employee empowerment on the intention to quit with performance as a mediating variable. Design/Methodology/Approach – This research uses quantitative methods and uses a population of 76 employees of Arya Mandiri Teknik Yogyakarta staff. Questionnaire method. Instrument test and classical assumption test. SEM-PLS program data analysis tool. Research Results–Employee empowerment has a positive and significant role in performance and Intention to Quit. Meanwhile, performance plays a positive and significant role in the Intention to Quit, and performance mediates the role of employee empowerment in the intention to quit. Originality – Research using established variables needs to be done as a reinforcement of existing theories, as well as contributing to the development of other, more specific variables